2020
DOI: 10.3390/ma13184088
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Analysis of a New Process for Forming Flanges on Hollow Parts

Abstract: The paper presented a new method for forming flanges on hollow parts by incremental radial extrusion. In the classic process of radial extrusion, additional rings were used to limit the free flow of material in the radial direction. The flange was formed progressively, using rings of increasing diameters. The proposed method was verified by numerical analysis and experimental tests. The numerical calculations were performed by the finite element method using the Deform-3D software package. Tubes made of alumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…The development of capabilities of the energy method of power balance based on the expansion of the base of kinematic modules of complex configuration was addressed in a series of works [29][30][31][32][33][34][35][36]. Papers [29,30] suggested techniques for simplifying the power of plastic deformation forces using a minimizing function in a general form.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of capabilities of the energy method of power balance based on the expansion of the base of kinematic modules of complex configuration was addressed in a series of works [29][30][31][32][33][34][35][36]. Papers [29,30] suggested techniques for simplifying the power of plastic deformation forces using a minimizing function in a general form.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The authors identified the complication of the mathematical apparatus when deriving the value of the reduced deformation pressure (in an analytical form) inside the kinematic module of a triangular or trapezoidal shape with slanting boundaries. A series of works attempted to resolve the issues related to searching for techniques to simplify the expressions of the reduced deformation pressure and deriving the appropriate engineering formulae for calculating the force regime of cold extrusion processes [33,34,36]. The variation of manufacturing modes, tool configurations in production significantly expands the possibilities of cold extrusion processes, on the one hand.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…To prevent the above mentioned phenomena, the process can be conducted with the use of limit rings for constraining free flow of metal in the flange forming zone. Studies have shown that incremental extrusion conducted with the use of both non-deformable rings [37] and deformable rings [38] results in significantly improved quality of extruded parts. The flange has a constant thickness and its maximum diameter is 30% bigger than that obtained in the process conducted without the use of a limit ring.…”
Section: Introductionmentioning
confidence: 99%
“…Another solution worthy of consideration is the new method for forming flanges on hollows parts by radial extrusion proposed by Winiarski et al [ 10 ]. The process was successfully applied to connect metal rings (sheets) to the metal tube ends, and is based on a force-fit joining mechanism relying on the residual normal pressures that are created at the contact interfaces after unloading.…”
Section: Introductionmentioning
confidence: 99%